2003
DOI: 10.1081/ncn-120023088
|View full text |Cite
|
Sign up to set email alerts
|

Endcaps for Stabilizing Short DNA Duplexes

Abstract: The syntheses of endcaps for covalently linking the 3' and 5' hydroxyl groups of blunt end double-stranded DNA are described. Endcap diols were converted into DMTr protected phosphoramidites and incorporated between nucleotides 4 and 5 of a self-complementary octamer. The stabilizing effect of the endcaps on duplex DNA was determined by Tm experiments on the self-complementary octamer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…It is evident from the study of the C12 hydrocarbon end-cap that the nature and length of the end-cap are important considerations in the design. This observation is supported by previous work conducted in the Bergstrom lab on the evaluation of spacers for use as dsDNA end-caps. The end-capped duplex stem in the capture modules confers high affinity and specificity for hybridization to overhanging sequences at the termini of pRNA overhybridization to the same sequence within the RNA. This specificity is due to the “preorganization” of the duplex stem region by the end-cap.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…It is evident from the study of the C12 hydrocarbon end-cap that the nature and length of the end-cap are important considerations in the design. This observation is supported by previous work conducted in the Bergstrom lab on the evaluation of spacers for use as dsDNA end-caps. The end-capped duplex stem in the capture modules confers high affinity and specificity for hybridization to overhanging sequences at the termini of pRNA overhybridization to the same sequence within the RNA. This specificity is due to the “preorganization” of the duplex stem region by the end-cap.…”
supporting
confidence: 64%
“…We believe that there is a way to rapidly and reversibly add modules to the 3′/5′-pRNA overhang that are small, have high affinity and specificity for the pRNA overhang, are simple to synthesize, and can link virtually any kind of molecule (including small ligands, peptides, lipids, carbohydrates, and fluorophores). Bergstrom and co-workers have utilized a method for stabilizing short segments of double-stranded oligonucleotides by covalently linking the 3′ and 5′ ends of the nucleic acid with a simple spacer. The simplest spacer is the C12 hydrocarbon ( S2 ) shown in Figure D. Nucleic acid duplexes containing just four base pairs and linked by a spacer at one end have melting temperatures ( T m values) in the range 41–62 °C (the same duplexes without the spacers are unstable at room temperature, i.e., T m < 25 °C).…”
mentioning
confidence: 99%
“…In addition, we prepared the terthiophene spacer 2 , which provided an opportunity to study and compare an exceptionally hydrophobic end-cap. Several research groups had reported that hydrophobic, aromatic molecules such as naphthalene diimides 32 − 34 ,, , N , N -dimethylstilbene dicarboxamide , trimethoxystilbenes, and stilbene ether stabilized DNA duplexes through stacking interactions with the DNA bases. We expected that end-cap 2 , with a terthiophene core, would also have significant stacking interactions with the base pairs in a DNA duplex.…”
Section: Resultsmentioning
confidence: 99%
“…[11,14] In summary, we have demonstrated the efficient templatedirected synthesis of hairpin metallosalen ± DNA conjugates (Ni-3 and Mn-3) and a metal-free salen ± DNA (EN-3). Templatedirected synthesis of hairpin structures, a demonstrated approach for the synthesis of DNA ± organic molecular conjugates, [15] has been extended to metal ± DNA hybrids.…”
Section: Template-directed Assembly Of Metallosalen ± Dna Hairpin Conmentioning
confidence: 98%